Soliton emissions at 1.59 and 1.95 μm utilizing nickel-trimesic acid metal-organic framework saturable absorber - Murad, Amir; Yusoff, Norita Mohd; Liew, Josephine Ying Chyi; Kaleem, Mohammad; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Mahdi, Mohd Adzir (Springer, 2024)
This study demonstrates the potential of nickel-trimesic acid, a material from the metal-organic framework (MOF) family, as a real saturable absorber (SA) for stable passively mode-locked pulse generation in erbium-doped fiber laser (EDFL) and thulium-holmium co-doped fiber laser (THDFL) ring cavities. The fabricated SA has modulation depths of 4.10% and 2.01%, and saturation intensities of 24.50 MW/cm2 and 14.50 MW/cm2, characterized at 1.56 μm and 2.00 μm, respectively. For EDFL, the mode-locked pulse centered at 1591.06 nm lasing wavelength was emitted with 3.19 nm spectral bandwidth and 1026 fs pulse width. Meanwhile, for THDFL, the generated pulse of 1410 fs was realized at 1951.60 nm central wavelength and 2.73 nm spectral bandwidth. The maximum average output power of 22.48 mW and 72.15 mW were measured from the EDFL and THDFL cavities, respectively. No perceptible variation of the optical spectrum and pulse width over one hour duration was observed for both laser cavities that indicated stable mode-locked pulse laser systems. These results demonstrate excellent performance from the nickel MOF-based SA and require further exploration of MOF-based SAs to enhance pulse mode-locking characteristics.